Comparison of indirect cathodic stripping voltammetric methods based on accumulation of mercury, copper(I) and nickel salts or complexes at a hanging mercury drop electrode : determination of 2-mercaptobenzot h iazole - Fogg, Arnold G.; Ismail, Razali; Ahmad, Rahmalan; Banica, Florin G. (Royal Society of Chemistry, 1996)
A preliminary study of the indirect cathodic stripping voltammetric determination of 2-mercaptobenzothiazole (MBT) based on accumulation of its mercury, copper(1) and nickel(I1) salts or complexes was made as part of a wider study comparing these three related techniques of determining thiols. Detection limits for MBT using the copper@) and nickel(I1) methods ( c 2 X considerably lower than that for the mercury method (about 3 x lo-' moll-1). The mercury method is susceptible to interference from copper(I1) and large amounts of nickel(@, and seems generally to be less reliable for the determination of MBT. The change from accumulation as the mercury salt to accumulation as the copper(1) salt is illustrated in the presence of excess of MBT over copper(@ with increasing copper(I1) concentrations, and with change of accumulation potential to more negative values from +lo0 mV. In the presence of a stoichiometric amount or excess of copper(I1) over MBT, no mercury salt is accumulated at potentials more negative than +50 mV. Currents obtained for MBT with the nickel(I1) method are much higher than those obtained previously with cysteine and penicillamine.